Estudio de factibilidad para la creación de un restaurant de comida vegetariana y bocaditos integrales en el cantón La Maná 2013 - Solís Laje, Mónica Yessenia (2015)
In assessing the feasibility of this project was studied to install a service company vegetarian restaurant in Canton La Maná 2013, through feasibility study, a market survey of the product was done by establishing the demand, supply prices and marketing channels. The technical study the operational process of the plant, location, equipment and machinery, supplies, and raw materials required are established. Through economic analysis all conditions of operation of a restaurant that turned the technical, such as initial investment, total costs, and installation of Business study were analyzed. Finally the financial evaluation was performed using indicators that demonstrated the viability of the investment, having a positive NPV and IRR 6678.13. Acceptable 39.36%. Whereas the net present value is greater than 0 the project is profitable and internal rate of return is higher than the interest rate on investment is feasible